Epidemiological profile of Road Traffic Accidents reporting at a Tertiary Care Hospital in Garhwal Region of Uttarakhand - Kandpal, S D; Vyas, Shaili; ., Deepshikha; Semwal, Jayanti (Indian Journal of Community Health, 2015)
Introduction: Accidents occur not only due to ignorance but also due to carelessness, thoughtlessness and over confidence. Human, vehicle and environmental factors play roles before, during and after a trauma event. Accidents, therefore, can best studied in terms of agent, host and environmental factors and epidemiologically classified into time, place and person distribution. Objective: To know the epidemiology of Road Traffic Injuries as seen in a Tertiary Care Hospital, Himalayan Hospital. Methodology: A cross-sectional study was done among patients of RTA admitted at a Tertiary Care Centre. A pretested semi-structured interview schedule was used to collect necessary information regarding the time, place and the person involved in the accident. Descriptive statistics for continuous variables and frequency, percentage for categorical variables were determined. Results: There was a marked male preponderance (83.24%) with maximum involvement of younger age groups. Most of the accidents had taken place in the evening hours (6 pm -12 midnight). Accidents were equally distributed throughout the year. Conclusion: Majority of the patients of RTI belonged to 21 to 30 years age group. Males out-numbered females victims.